Draft Five Year Plan 1978-83 Industry Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
In order to give a filip to development of Industries, infrastructure facilities were extended initially in the form of giving built up sheds in industrial estates in 19 districts. Secondly, industrial areas have been developed in 24 districts. Besides these, there are rural work sheds and semi urban industrial estates, the intention being to give the basic infrastructure like developed sites, road, water, electricity etc. There are total number of 1850 acres of land developed in these pieces and 733 number of sheds constructed in these places out of which 1500 acres have already been allotted to industries. The balance is in the process of being allotted to the new industries 660 sheds have already been allotted to the entrepreneurs.
Government of Madhya Pradesh, Planning, Economics and Statistics Department